Analisis Strategis Pengembangan Sektor Ekonomi Unggulan Kabupaten /Kota Di Provinsi Maluku - Metubun, Giovanny Gwynne; Leiwakabessy, Erly; Hahury, Hendri Dony (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to 1) Determine the potential of leading economic sectors of Regency/City in Maluku Province. 2) To formulate a potential Development strategy for the leading economic sectors of Regency/City in Maluku Province. The analytical tools used in this research are Static Location Quatient (SLQ), Dynamic Location Quatient (DLQ), Growth Ratio Model (MRP) and Klassen Typology and Development Strategy using the Boston Consulting Group (BCG) Matrix. The results based on the analysis of SLQ, DLQ, MRP and Klassen Typology, shows that the leading economic sector of Tanimbar Islands Regency is 1 sector. Southeast Maluku Regency 1 sector, Central Maluku Regency; 1 sector . Buru Regency; 1 sector, Aru Islands Regency 1 sector, West Seram Regency 1 sector East Seram Regency does not have a selected leading sector. Southwest Maluku Regency has 2 leading sectors, South Buru Regency has 1 leading sector. Ambon City has 3 selected leading sectors. Tual City has 1 leading sector. Meanwhile, the Development Strategy that can be carried out through Boston Consulting Group (BCG) Matrix analysis is the Hold Strategy, the strategy is to maintain economic sectors that are in the leading classification so that it remain in the same category and strive to be encouraged by the best investment climate and the Build strategy, is to increasing the investment in economic sectors that have a large contribution so that it can increase market share.